DED process parameters optimization via experiments - Lee, Anthony Kai Zhe (Nanyang Technological University, 2023)
The additive manufacturing (AM) technique Directed Energy Deposition (DED) specializes in mending, quick prototyping, and low-volume part manufacturing. Due to its tremendous advantages, it is commonly employed in various sectors, such as aerospace, healthcare, and the military. A common material to work with is 316L stainless steel because of its excellent tensile and corrosion-resistant qualities. For this project, 5 process parameters (Laser Power, Scanning Speed, Powder Mass flow rate, XY-Incremental ratio, and Z Incremental ratio) were varied with different values to get a correlation with the microstructure parameters (Grain Area, Grain Ellipse aspect ratio, and Grain angle) and the mechanical property (Ultimate Tensile Strength) of a multi-layer multi-track deposition. The microstructure was analysed using Electron Backscatter Diffraction (EBSD) method and a relationship between the process parameters, microstructure parameters, and the ultimate tensile strength was concluded.